Comparison of exergoeconomic analysis of two different perlite expansion furnaces - Gurturk, Mert; Öztop, Hakan Fehmi; Hepbasli, Arif (Pergamon-Elsevier Science Ltd, 2015)
In this study, exergoeconomic analyses of two different perlite expansion furnaces are performed based on the actual operational data. The exergy cost and the cost per unit of exergy of the expanded perlite produced by the Former Perlite Expansion Furnace (FPEF) are determined to be 62.886 US$/h and 648.309 US5/GJ while those produced by the New Perlite Expansion Furnace (NPEF) are obtained to be 106.734 US$/h and 503.463 US5/GJ, respectively. Additionally, the production costs based on exergy are calculated to be 0.153 US$/kg for the FPEF and 0.102 US$/kg for the NPEF. The production costs based exergy and exergoeconomic factor of the FPEF are found to be 0.153 US$/kg and 45%. Those of the NPEF are obtained to be 0.102 US$/kg and the 67%. A novel method is also proposed for calculating the exergy cost per unit of the fuel. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Exergoeconomic; Furnace; Perlite